#TITLE_ALTERNATIVE# - TAUFIK AKBAR (NIM. 20208017), FIKI
The Ricci flow, which connects metric evolution and curvature of space, was introduced by Richard Hamilton in 1982 in order to gain insight into the geometrization conjecture of William Thurston, concerning the topological classification of three dimensional smooth manifolds. In this thesis, we study some aspects of perturbative solutions of Ricci flow equation in four dimensional spacetime that admits a spherical symmetric metric. Two cases are considered, namely Ricci flat and Einstein metric cases. Then, we derive the surface gravity for both cases. We find that in both cases, surface gravity does not depend on a parameter T (tau).